GRADE: Assessing the quality of evidence in environmental and occupational health. (July 2016) - Morgan, Rebecca L.; Thayer, Kristina A.; Bero, Lisa; Bruce, Nigel; Falck-Ytter, Yngve; Ghersi, Davina; Guyatt, Gordon; Hooijmans, Carlijn; Langendam, Miranda; Mandrioli, Daniele; Mustafa, Reem A.; Rehfuess, Eva A.; et al.
Abstract: There is high demand in environmental health for adoption of a structured process that evaluates and integrates evidence while making decisions and recommendations transparent. The Grading of Recommendations Assessment, Development and Evaluation (GRADE) framework holds promise to address this demand. For over a decade, GRADE has been applied successfully to areas of clinical medicine, public health, and health policy, but experience with GRADE in environmental and occupational health is just beginning. Environmental and occupational health questions focus on understanding whether an exposure is a potential health hazard or risk, assessing the exposure to understand the extent and magnitude of risk, and exploring interventions to mitigate exposure or risk. Although GRADE offers many advantages, including its flexibility and methodological rigor, there are features of the different sources of evidence used in environmental and occupational health that will require further consideration to assess the need for method refinement. An issue that requires particular attention is the evaluation and integration of evidence from human, animal, in vitro, and in silico (computer modeling) studies when determining whether an environmental factor represents a potential health hazard or risk. Assessment of the hazard of exposures can produce analyses for use in the GRADE evidence-to-decision (EtD) framework to inform risk-management decisions about removing harmful exposures or mitigating risks. The EtD framework allows for grading the strength of the recommendations based on judgments of the certainty in the evidence (also known as quality of the evidence), as well as other factors that inform recommendations such as social values and preferences, resource implications, and benefits. GRADE represents an untapped opportunity for environmental and occupational health to make evidence-based recommendations in a systematic and transparent manner. The objectives of this article are to provide an overview of GRADE, discuss GRADE's applicability to environmental health, and identify priority areas for method assessment and development. Highlights: A structured framework is needed for decision-making in environmental health. GRADE has been applied in many disciplines and holds great promise for the field. Methods development and assessment is needed to address environmental health data. Methods assessment priorities are evaluation and integration of diverse evidence streams. GRADE evidence-to-decision framework informs risk and other management decisions.